2006
DOI: 10.1016/j.neuron.2006.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A Role in Learning for SRF: Deletion in the Adult Forebrain Disrupts LTD and the Formation of an Immediate Memory of a Novel Context

Abstract: Whereas significant insight exists as to how LTP-related changes can contribute to the formation of long-term memory, little is known about the role of hippocampal LTD-like changes in learning and memory storage. We describe a mouse lacking the transcription factor SRF in the adult forebrain. This mouse could not acquire a hippocampus-based immediate memory for a novel context even across a few minute timespan, which led to a profound but selective deficit in explicit spatial memory. These animals were also im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
184
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(196 citation statements)
references
References 84 publications
11
184
0
1
Order By: Relevance
“…Furthermore, mice with lesions of the mPFC were able to master the nonmatching-to-position rule with the same rate as their control group did. There was no evidence of a lesion-induced deficit in locomotor activity, and similar findings were reported in two recent lesion studies (23,24). Taken together, these findings indicate that lesions of the mPFC did not compromise processing of attention or spatial information and did not produce a global learning, motivational, or motor deficit; rather, the lesions appear to affect specifically the ability of mice to learn the DNMTP task with proactive interference in the eight-arm radial maze.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, mice with lesions of the mPFC were able to master the nonmatching-to-position rule with the same rate as their control group did. There was no evidence of a lesion-induced deficit in locomotor activity, and similar findings were reported in two recent lesion studies (23,24). Taken together, these findings indicate that lesions of the mPFC did not compromise processing of attention or spatial information and did not produce a global learning, motivational, or motor deficit; rather, the lesions appear to affect specifically the ability of mice to learn the DNMTP task with proactive interference in the eight-arm radial maze.…”
Section: Discussionsupporting
confidence: 87%
“…These findings suggest a correlation between LTD and novelty detection during learning. Notably, LTD-null mice lacking serum response factor (SRF) failed to habituate to novel objects in an object-recognition task (44). It is interesting that SRF-knockout mice also display poor spatial memory in MWM, paralleling the presently observed effect of acute LTD blockade on spatial memory consolidation.…”
Section: Discussionmentioning
confidence: 90%
“…Further evaluation of a forebrain SRF-knockout mouse model showed no change in the neuronal number; however, behavioral studies showed deficits in habituation to a novel spatial stimulus and defective memory and learning. 82 Microarray profiling of the hippocampi from this SRFknockout mouse showed attenuated expression of the genes involved in the release of calcium (eg, ryanodine receptors 1 and 3), although again, it is unclear whether these are direct or indirect SRF-target genes. 82 Alzheimer's disease (AD) is the most common form of dementia and represents, arguably, one of the most challenging ailments confronting the World Health Organization as no effective treatment exists to prevent or slow disease progression.…”
Section: Srf and Nervous System Disease Central Nervous Systemmentioning
confidence: 93%
“…82 Microarray profiling of the hippocampi from this SRFknockout mouse showed attenuated expression of the genes involved in the release of calcium (eg, ryanodine receptors 1 and 3), although again, it is unclear whether these are direct or indirect SRF-target genes. 82 Alzheimer's disease (AD) is the most common form of dementia and represents, arguably, one of the most challenging ailments confronting the World Health Organization as no effective treatment exists to prevent or slow disease progression. Furthermore, AD is very difficult to accurately diagnose in patients, and there is an expected sharp increase in the number of people who will acquire AD.…”
Section: Srf and Nervous System Disease Central Nervous Systemmentioning
confidence: 93%